PELINDUNGAN PATEN DALAM PERSPEKTIF FUNGSI HUKUM SEBAGAI KONTROL SOSIAL DAN REKAYASA SOSIAL: - - Sudjana Sudjana (Faculty of Law, Maranatha Christian University, 2021)
Law is a means of social control to direct people to take actions in accordance with applicable regulations so as to create order and peace. While the function of law as social engineering is to change human behavior in order to uphold justice and respect obligations under the law. This study aims to determine the function of law as social control and social engineering related to patent protection. The research method used is a descriptive analytical approach to legislation. Data collection was carried out through literature study while data analysis was carried out in a qualitative normative manner. The results of the study show that the legal function as social control related to patents is the object, terms and procedures of protection and the period of protection, while the subject of protection and legal action in case of violation is the function of law as social engineering. However, in order to understand the requirements for granting patents and to eliminate the impression that patent registration is too procedural and to increase legal awareness in order to respect patents by other parties, it is necessary to continuously disseminate information or information through print or electronic media with the use of technological means which are currently developing rapidly so that can support the effectiveness of social control and social engineering as mandated by the Patent Law.